Civil rights marches - George, Linda (New York Children's Press, 1999)
Describes the peaceful marches in the United States on behalf of civil rights for blacks from the 1950s to the 1990s, including the March on Washington and other important marches
Hurg
5
Keywords: African Americans -- Civil rights; Race relations